Assembly Sequence Flexibility – Assembly Precedence Matrix-Based Evaluation Model - Marco Bleckmann; Luca Mastroianni; Meret Borgerding; Peter Nyhuis (IEEE Access, 2025)
The dimensioning and design of assembly operating equipment (AOE), such as workpiece carriers, assembly devices, and assembly assistive devices, are central to the early phase of many processes in assembly planning. In addition to the traditional economic requirements, production-related factors such as assembly sequence flexibility (ASF) are increasingly important. The characteristics and design of AOE result in restrictions about assembly precedence relationships, which must be considered when assigning assembly contents to workstations. In the assembly planning process, the restrictions imposed by the product can only be influenced to a limited extent. In particular, combining different product variants on a standard assembly system according to the flow principle results in a complex network of assembly precedence relationships that can affect productivity. It is because assembly line balancing can only be implemented to a limited extent, or the compatibility of different product variants within the same assembly system is insufficient. This paper presents a developed general approach using assembly precedence matrices (APMs) that allows further analysis by integrating additional information. This approach evaluates the constraints caused by AOE and analyzes or prioritizes their elimination in terms of ASF. To validate the proposed model, a practical implementation follows in a learning factory, where an exemplary product is evaluated in terms of its ASF when implemented in an assembly system based on the flow principle.